1994
DOI: 10.1111/j.1365-3059.1994.tb00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity testing and assessment of the pathogenicity of the rust, Puccinia abrupta var. partheniicola, as a biological control agent of Parthenium weed (Parthenium hysterophorus)

Abstract: Parthenium hysterophorus, a native of Central America, is a problem weed of Australian rangeland, particularly in Queensland. Following field surveys in Mexico, the rust fungus Puccinia abrupta var. partheniicola was selected as a potential biological control agent. One isolate was chosen for further investigation after infection studies with one Kenyan and five Mexican isolates. Assessment of inoculation conditions showed that temperatures of less than 20° C and dew periods of more than 6 hours were required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…It has been suggested that host specificity tests of microbial pathogens should be conducted under controlled conditions to facilitate optimum infection and disease development on test plants (Watson, 1985). However, these artificial conditions can predispose plants to infection and may artificially increase the perceived host range of the organism being tested (Adams, 1988;Parker et al, 1994;Watson, 1985). Other Puccinia spp.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that host specificity tests of microbial pathogens should be conducted under controlled conditions to facilitate optimum infection and disease development on test plants (Watson, 1985). However, these artificial conditions can predispose plants to infection and may artificially increase the perceived host range of the organism being tested (Adams, 1988;Parker et al, 1994;Watson, 1985). Other Puccinia spp.…”
Section: Discussionmentioning
confidence: 99%
“…The technique is easy to perform and has the advantage of allowing a relatively rapid examination of the rust infection process on leaf samples of weeds and cultivated plants (Bruzzese and Hasan 1983). It has been shown to work very well with whole leaf portions of the flat leaves of dicotyledonous species (Bruzzese and Hasan 1986;Evans and Tomley 1994;Parker et al 1994) or of some grass species such as Dactylis glomerata (Bruzzese and Hasan 1983), maize, oat, or wheat (personal observations).…”
Section: Whole Leaf Clearing and Staining Techniquementioning
confidence: 97%
“…The whole leaf clearing-staining technique proposed by Bruzzese and Hasan (1983) has been included in the host range testing of many rust fungi selected as prospective candidates in biological control programs, especially in projects in which a high number of species must be tested against the pathogen (Bruzzese and Hasan 1986;Evans and Tomley 1994;Parker et al 1994). The technique is easy to perform and has the advantage of allowing a relatively rapid examination of the rust infection process on leaf samples of weeds and cultivated plants (Bruzzese and Hasan 1983).…”
Section: Whole Leaf Clearing and Staining Techniquementioning
confidence: 99%
“…Nonetheless, such native-range studies are seldom carried out to assist the selection process of pathogens. While controlled-environment experiments are also sometimes performed to measure the pathogen's impact (Parker et al 1994;Shishkoff & Bruckart 1996;Evans & Bruzzese 2003;Berner & Bruckart 2005), results are generally inadequate to make sound predictions of field impact under varying and often less than optimum conditions. Only once has a limited field trial of an exotic pathogen (Puccinia carduorum Jacky) in the introduced range of the target weed (musk thistle; Carduus nutans) been approved prior to large-scale releases (Baudoin et al 1993).…”
Section: Pathogen Taxonomy and Life Cyclementioning
confidence: 98%